A classification proposal of digital twin applications in the safety domain. (April 2021) - Agnusdei, Giulio Paolo; Elia, Valerio; Gnoni, Maria Grazia
Highlights: Digital Twins (DTs) are wide spreading in manufacturing; few applications are in the safety domain. A three-dimensional general framework to evaluate DT complexity is proposed. The framework overlaps DT technological features with safety issues. A content analysis of the literature has been performed based on the proposed framework. Abstract: The increasing diffusion of digitalization in industry and society is forcing the adopting of tools based on new enabling technologies. This phenomenon is clearly observable in the manufacturing sector, where, due to the diffusion of Industry 4.0 paradigm, physical processes are integrating effectively with digital ones. One recent innovative technology is the Digital Twin (DT), where digital models and physical ones communicate – by sharing data as well as information – usually in a bidirectional way. As recent studies have analyzed the current level of adoption of DT technologies in the manufacturing sector, less effort has been focused on evaluating applications in the safety domain. Theoretically, the DT inherent capability of acquiring data from the physical world - usually developed in real time – together with the potentiality of reliable data processing could support a more effective diffusion of dynamic risk assessment models as well as real time alert management systems for improving safety. Otherwise, the actual capability of real applications highly depends on the level of complexity of the specific DT. The aim of the study is to provide a methodology to assess current application of DT technologies; the framework has been developed in the safety domain aiming to point out to researchers as well as technicians in a clear way the capabilities of a specific DT application. The framework has been adopted for analyzing current applications of DT in the scientific literature aiming to propose a theoretical validation. The application has outlined that, although the number of DT applications in the safety field is not so large, the current tools developed are characterized by a high level of complexity thus providing higher reliability to support the specific safety problem in analysis. Further developments will be oriented towards developing a quantitative assessment framework to integrate the proposed tool.